Cruise passengers’ perception of key quality attributes of cruise lines in North America - Chua, Bee-Lia; Ben, Goh; Huffman, Lynn; Jai, Catherine; Karim, Shahrim (Taylor & Francis, 2016)
This study identified cruise passengers’ perceived importance and performance of quality attributes for cruise lines in North America by utilizing an importance–performance analysis tool. The results concluded that: (a) room temperature, behavior of other passengers, food and beverages, and accommodation require immediate attention from cruise line operators; (b) the cruise lines are succeeding in providing excellent services for their customers, as well as maintaining a high level of overall shipboard cleanliness; and (c) cruise marketing efforts should promote the attractiveness of onboard activities and facilities, including entertainment, recreation and sports facilities, fitness and health facilities, supplementary facilities, and facilities for children. Overall, the results of this study help cruise lines identify which onboard attributes need more attention and determine the areas that may be consuming too many resources.